Barriers to care linkage and educational impact on unnecessary MASLD referrals - Lee, Jun-Hyuk; Yoon, Eileen Laurel; Oh, Ju Hyun; Kim, Kyunam; Ahn, Sang Bong; Jun, Dae Won (Frontiers in Medicine, 2024)
Background: The importance of primary care physicians (PCPs) in managing metabolic dysfunction-associated steatotic liver disease (MASLD) has increased. This study aimed to assess the effectiveness of an online educational program on MASLD among physicians. Methods: In total, 869 physicians (72 physicians at referral centers and 797 PCPs) participated in this study. They completed an initial survey regarding their clinical practices for patients with MASLD, followed by a second online survey eight weeks after receiving a series of seven weekly sets of educational materials on MASLD. Results: In the baseline survey, most PCPs did not routinely evaluate the stage of hepatic fibrosis in MASLD; they typically initiated assessments based on elevated liver enzyme levels. Only a limited number of PCPs used vibration-controlled transient elastography. The main hurdles in managing MASLD were “the absence of a fee for patient education” for PCPs and “short consultation time” for referral-center physicians. In the follow-up survey, the percentage of liver fibrosis assessments using noninvasive tests increased from 7.0% to 11.2%. Additionally, evaluations for cardiovascular disease increased from 3.9% to 8.2%, and the risk of ischemic stroke increased from 13.7% to 16.9%. The percentage of immediate referrals of patients to specialists after an MASLD diagnosis decreased from 15.4% to 12.3%. Conclusions: The discrepancies in management strategies and viewpoints regarding MASLD between PCPs and referral-center physicians can hinder efforts to mitigate the disease burden. Increasing awareness among PCPs regarding MASLD through a seven-week education program led to a reduction in unnecessary referral rates and an increase in cardiovascular evaluations.